Honeycomb metal substrate and catalytic converter
By forming pores and burrs of specific structures on the honeycomb metal substrate of the catalytic converter and covering the oxide coating film containing α-alumina, the shortcomings of the catalytic converter in emission control and catalyst aging are solved, and the catalytic converter is achieved Better emission control performance and catalyst stability.
Patent Information
- Application Number
- CN202280053604.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-17
- Filing Date
- 2022-05-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-05-12
AI Technical Summary
Existing catalytic converters have shortcomings in emission control performance and catalyst aging, especially in the absence of emission control during cold start-up, and the catalyst deteriorates due to aging.
A honeycomb metal substrate formed by alternately laminating metal flat foil and metal corrugated foil is used, and multiple holes and small height burrs are formed on its surface. The burr surface is covered with an oxide coating film containing α-alumina to meet the specific Pore size, pore size ratio and burr height range.
The emission control performance of the catalytic converter is improved, the deterioration of the catalyst is reduced, the catalytic reaction is activated through the reaction source effect, and the abnormal temperature rise of the catalyst is reduced through the oxide coating film.
Smart Images

Figure CN117858760B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a honeycomb metal substrate, which is formed by alternately laminating metal flat foils and metal corrugated foils. Background Art
[0002] As a catalyst substrate for removing pollutants from exhaust gas of an internal combustion engine of an automobile or the like, there is known a catalytic converter formed by inserting a honeycomb body made of a heat-resistant alloy into a housing made of a heat-resistant alloy. In the catalytic converter, particularly in a metal substrate made of metal foil, a honeycomb body formed by alternately laminating a metal flat foil having a thickness of about 50 μm and a corrugated foil obtained by corrugating the flat foil, or a honeycomb body formed by overlapping and spirally winding a strip-shaped flat foil and a corrugated foil, etc. has been used.
[0003] In recent years, automobile emission regulations have tended to become more stringent, and the emission of harmful substances such as carbon monoxide, hydrocarbons, and nitrogen oxides, especially during cold start in an emission measurement mode, accounts for a significant proportion of the total emission; therefore, it is necessary to activate the catalyst as early as possible. Therefore, various metal substrates have been proposed, in which a flat foil and a corrugated foil included in the metal substrate are subjected to a pore-forming treatment to generate turbulence, thereby enhancing emission control performance.
[0004] Patent Document 1 discloses a technology for improving flow characteristics in a honeycomb body and improving material exchange between the surface and the flow caused by this improvement by appropriately determining the number, size and distribution of pores to thereby improve emission control performance.
[0005] Patent document 2 discloses a catalytic converter having excellent high temperature durability, the catalytic converter mainly comprising a metal foil in which a plurality of holes are formed and the holes have an improved brazing position. Patent document 3 discloses a technology in which, in a metal catalyst substrate including a corrugated plate and a flat plate in which a plurality of slit holes are formed, an annular protrusion protruding from the corrugated plate and the flat plate is formed at an opening edge of each slit hole, and exhaust gas is made to collide with the annular protrusion to generate turbulence, thereby enhancing emission control performance.
[0006] Patent document 4 discloses a catalytic converter for removing pollutants from exhaust gas, the catalytic converter comprising a metal honeycomb substrate made by machining a stainless steel foil and a catalyst layer formed on the stainless steel foil, the stainless steel foil containing at least Fe, Cr, and Al, an oxide coating film produced by oxidation of the stainless steel foil components being formed on the surface of the stainless steel foil, the concentration of Fe contained in the oxide coating film being in the range of 0.1% to 7% expressed as mass % relative to the oxide. Patent document 4 also discloses that the migration of Fe in the foil into the catalyst layer is reduced by means of the oxide coating film containing Fe, and thus the degradation of the catalyst due to Fe is reduced.
[0007] The formation of holes in a metal foil for a honeycomb is accompanied by the formation of burrs on the edges of the holes as in Patent Documents 1 to 3. The burrs, which are undesirable protrusions, are often removed by a deburring step.
[0008] Citation List
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 4975969
[0011] Patent Document 2: Japanese Patent No. 5199291
[0012] Patent Document 3: Japanese Patent Application Publication No. 2005-313083
[0013] Patent Document 4: Japanese Patent Application Publication No. 2007-203256 Summary of the invention
[0014] Technical issues
[0015] The present inventors have found that the emission control performance is improved by leaving the burrs formed around the holes. At the same time, the present inventors have found a problem that the catalyst around the burrs deteriorates due to aging.
[0016] An object of the present invention is to improve the emission control performance of a catalytic converter and to reduce catalyst degradation.
[0017] Problem Solution
[0018] In order to solve the above problems, (A) a honeycomb type metal substrate is formed by alternately laminating metal flat foils and metal corrugated foils,
[0019] A plurality of holes are formed in a metal flat foil and a metal corrugated foil, a burr having a small height is formed on the edge of each hole, and in the metal flat foil and the metal corrugated foil, at least the surface of the burr is covered with an oxide coating film containing α-alumina, when the average pore size of the plurality of holes is defined as D, the pore size ratio is defined as R, and the average height of the burr is defined as L, the following equations (1) to (3) are satisfied,
[0020] 0.2mm≤D≤4.0mm (1)
[0021] 5%≤R≤70% (2)
[0022] 0.1μm≤L≤30μm (3).
[0023] (B) The honeycomb type metal substrate according to (A), wherein the tip end surface of each burr is formed into a shape extending in a direction orthogonal to a protruding direction of the burr.
[0024] (C) The honeycomb type metal substrate according to (B), wherein the burrs have narrow portions each having a smaller width than a tip end surface.
[0025] (D) The honeycomb metal substrate according to any one of (A) to (C), wherein the average height L of the burrs satisfies the following equation (4),
[0026] 0.5μm≤L≤20μm (4).
[0027] (E) A catalytic converter comprising: a honeycomb metal substrate according to any one of (A) to (C); and a catalyst layer carried on a metal flat foil and a metal corrugated foil, wherein an average height L of the burrs is less than the thickness of the catalyst layer or is greater than the thickness of the catalyst layer by a predetermined amount, and the predetermined amount is 10 μm or less.
[0028] (F) A catalytic converter comprising: a honeycomb metal substrate according to (D); and a catalyst layer supported on a metal flat foil and a metal corrugated foil, wherein an average height of the burrs L is smaller than a thickness of the catalyst layer.
[0029] (G) In (A) to (F), the oxide coating film may have a thickness in the range of 0.05 μm to 2 μm, and contain at least 10% by mass or more of α-alumina.
[0030] Beneficial effects of the present invention
[0031] The present invention makes it possible to achieve both improved emission control performance of a catalytic converter and reduced degradation of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] [ Figure 1] is a perspective view of a catalytic converter.
[0033] [ Figure 2 ] is a cross-sectional view of a portion of a honeycomb body.
[0034] [ Figure 3 ] is a photograph of a cross section of a burr before shape adjustment.
[0035] [ Figure 4 ] is a photograph of a cross section of the burr after shape adjustment.
[0036] [ Figure 5 ] is a schematic diagram of the tip surface of a burr extending around a hole.
[0037] [ Figure 6 ] is a plan view of a catalytic converter used to explain a method of calculating the average height of the burrs L.
[0038] [ Figure 7 ] is a schematic diagram of the shape adjustment device.
[0039] [ Figure 8 ] is a diagram used to explain the aperture ratio R.
[0040] [ Fig. 9 ] is a photograph of the cross section of the burr after shape adjustment (deformation example).
[0041] [ Fig.10 ] is a cross-sectional view of a portion of a honeycomb body (second embodiment). DETAILED DESCRIPTION
[0042] (First Embodiment)
[0043] Preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. Figure 1 is a perspective view of the catalytic converter 1, and the axial direction of the catalytic converter 1 is indicated by a double arrow. The catalytic converter 1 includes: a honeycomb body (corresponding to a honeycomb type metal substrate) 4, which is formed by spirally winding a flat foil 2 and a corrugated foil 3 into a wound body; and an outer cover 5, which surrounds the outer peripheral surface of the honeycomb body 4. It should be noted that the honeycomb body 4 may also be a laminated body formed by alternately stacking the flat foil 2 and the corrugated foil 3. Either of the wound body and the laminated body has a structure in which the flat foil 2 and the corrugated foil 3 are stacked when viewed in a cross section. Therefore, the honeycomb type metal substrate set forth in the claims includes not only a laminated body but also a wound body.
[0044] A metal foil made of a heat-resistant alloy can be used for the flat foil 2 and the corrugated foil 3. The thickness of the metal foil is preferably 20 μm or more and 100 μm or less. The width of the metal foil is preferably 10 mm or more and 500 mm or less. The size of the metal foil may be changed as appropriate depending on the application of the catalytic converter 1. The corrugated foil 3 can be manufactured, for example, by corrugating a metal flat foil.
[0045] Here, a stainless steel foil containing aluminum can be used as the heat-resistant alloy. Ferritic stainless steel containing Cr: 20 mass %, Al: 3 mass % to 8 mass % and the balance being Fe and inevitable impurities can be used as this type of stainless steel foil.
[0046] It should be noted that the heat-resistant alloy applicable to the present invention is not limited to the above-mentioned ferritic stainless steel, and various heat-resistant stainless steels containing Al in the alloy composition can be widely used. That is, the metal foil used for the honeycomb body 4 often contains 15% to 25% by mass of Cr and 2% to 8% by mass of Al, and Fe-18Cr-3Al alloy, Fe-20Cr-8Al alloy, etc. can also be used as the heat-resistant alloy.
[0047] The catalyst can be supported on the metal foil by applying a predetermined washcoat liquid to the surface of the metal foil of the honeycomb body 4, and drying and firing the washcoat liquid. For the washcoat liquid, for example, a slurry obtained by stirring γ-alumina powder, lanthanum oxide, zirconium oxide, and cerium oxide in an aqueous palladium nitrate solution can be used.
[0048] For example, stainless steel may be used for the outer cover 5. The thickness of the outer cover 5 is preferably 0.5 mm or more and 3 mm or less. The cell density of the honeycomb body 4 is preferably 100 cells to 600 cells per square inch.
[0049] The catalytic converter 1 is arranged in an exhaust pipe (not shown) of a vehicle so that exhaust gas can flow in from one end side and can be discharged from the other end side in the axial direction. The reaction of the catalyst supported on the catalytic converter 1 with the exhaust gas removes pollutants from the exhaust gas that has flowed into the catalytic converter 1.
[0050] Figure 2is a cross-sectional view of a portion of a honeycomb body 4 cut in a radial direction. Both the flat foil 2 and the corrugated foil 3 include a plurality of holes 8 penetrating the foil in the thickness direction. There is no particular restriction on the arrangement of the holes 8, for example, in an expanded state before forming the honeycomb body 4, a metal foil in which the holes 8 are formed in a checkerboard pattern or a zigzag pattern can be used. Generally, the air flow in a metal substrate including a metal foil without holes is laminar flow. When the metal foil has holes, the Reynolds number in the porous portion is partially increased, and turbulence is easily generated; and therefore, the emission control performance is improved. However, excessive turbulence is not preferred because it leads to increased pressure loss. The present invention suppresses excessive turbulence by limiting the aperture and aperture ratio of the holes 8 to a predetermined range and by limiting the height of the burrs to a small height; and the degradation of the emission control performance caused by the limitation of turbulence is compensated by the reaction source (in other words, the ignition source) effect of the burrs. This will be described in detail later.
[0051] Burrs 2A are formed on the edges of each hole 8 of the flat foil 2, which are embedded in the catalyst layer 20 and extend in the circumferential direction. Burrs 3A are formed on the edges of each hole 8 of the corrugated foil 3, which are embedded in the catalyst layer 20 and extend in the circumferential direction. Burrs 2A, 3A are protrusions naturally formed when a hole is formed in a metal foil using a hole-making tool, and are also called flash. Since burrs are generally unnecessary protrusions, they are removed in the deburring step; however, in the present invention, by performing a shape adjustment step, the burrs are left as a structure for improving emission control performance. Although the type of hole-making tool is not particularly limited, continuous hole forming can be performed using a mold of a punch press, a rotary punch, or the like.
[0052] An oxide coating containing α-alumina is formed on the surface of the flat foil 2 and the corrugated foil 3. The oxide coating is also formed on the surface of the burrs 2A, 3A. By heating the honeycomb 4 in an oxidizing atmosphere having a temperature exceeding 800° C., an oxide coating is formed on the surface of the flat foil 2 and the corrugated foil 3 (including the surface of the burrs). In the case where the metal foil used as the flat foil 2 and the corrugated foil 3 is a ferritic stainless steel foil containing Cr: 20 mass%, Al: 3 mass% to 8 mass% and the balance being Fe and inevitable impurities, an oxide coating containing at least 10 mass% or more of α-alumina is formed on the surface of the stainless steel foil by applying the above-mentioned oxidation treatment (heat treatment) to the honeycomb 4. In addition to α-alumina, the oxide coating may also contain chromium oxide and iron oxide.
[0053] The thickness of the oxide coating is preferably in the range of 0.05 μm to 2 μm. As long as the thickness of the oxide coating containing at least 10% by mass or more of α-aluminum oxide is 0.05 μm or more, the degradation of the catalyst due to aging can be reduced. Making the thickness of the oxide coating 2 μm or less makes it possible to reduce the durability of the flat foil 2 and the corrugated foil 3. The thickness of the oxide coating increases as the content of aluminum contained in the stainless steel foil increases.
[0054] Will refer to Figure 3 , Figure 4 and Figure 5 The structure of the burrs 2A and 3A will be described in detail. Figure 3 This is a photograph of a cross section of a burr before shape adjustment (in other words, the burr just after punching). Figure 4 This is a photograph of a cross section of the burr after shape adjustment. Figure 5 is a schematic diagram showing the tip surface of a burr extending around a hole.
[0055] refer to Figure 3 The burrs before shape adjustment have sharp tips; therefore, when the catalyst layer is formed on a flat foil (corrugated foil), the burrs protrude excessively from the catalyst layer. In this case, the exhaust gas collides with the burrs protruding from the catalyst layer, which causes excessive turbulence and increased pressure loss.
[0056] Reference Figure 4 The tip surface of the burr 2A, 3A extends in a direction orthogonal to the protruding direction of the burr. The protruding direction of the burr is the thickness direction of the metal foil. Figure 5 As shown by the hatching in FIG. 8 , the term “extend” means that “the tip surface of the burr 2A, 3A exists and extends in the radial direction from the edge of the hole 8”; and the degree of extension at each circumferential position is not necessarily uniform. In addition, the tip surface of the burr 2A, 3A may be flat, or have fine irregularities formed thereon.
[0057] Further, if Figure 4 As shown, the burrs 2A, 3A are each formed to have a narrow portion 50; and when the width of the tip surface is defined as P1 and the width of the narrow portion 50 is defined as P2, the magnitude relationship between P1 and P2 is P1>P2. The width means the width of each hole 8 in the radial direction.
[0058] By providing the burrs 2A, 3A with a small height, the emission control performance of the catalytic converter 1 can be improved. The reason is presumed to be as follows. The burrs 2A, 3A with a small height have a small heat capacity, and the temperature tends to rise when the exhaust gas flows in. On the other hand, since these burrs are buried in the catalyst layer 20, the accumulated heat is difficult to be taken away by the gas.
[0059] Therefore, despite the low exhaust gas temperature, the expansion of the catalytic reaction region starting from the burr occurs, and thus the catalytic reaction of the honeycomb body 4 as a whole is activated.
[0060] In other words, the catalyst supported on and around the burr acts as a reaction source that determines the start and end of the catalytic reaction, and by lowering the temperature of the exhaust gas when the reaction source is generated and disappears, the catalytic reaction can be activated at an early stage. In the following description, the effect achieved by the burrs 2A, 3A is also referred to as a reaction source effect. By forming each tip surface of the burrs 2A, 3A into a shape extending in a direction orthogonal to the protruding direction of the burrs, the contact area with the catalyst is increased compared to burrs having the same height and sharp ends (including the burrs of the second embodiment below) and the above-mentioned reaction source effect can be enhanced.
[0061] Meanwhile, the inventors have discovered the following problem: when a catalytic converter 1 (i.e., a catalytic converter outside the scope of the present invention) is used to purify exhaust gas, degradation of the catalyst due to aging increases. As a result of a detailed study on this issue, it has been speculated that the catalyst near the burrs 2A, 3A undergoes abnormal temperature rise and deteriorates. Then, it has been found that a means for reducing the degradation of the catalyst is to form an oxide coating containing α-alumina on each of the surfaces of the burrs 2A, 3A. In other words, by forming an oxide coating containing α-alumina on each of the surfaces of the burrs 2A, 3A, heat transfer between the burrs 2A, 3A and the catalyst is promoted. This makes it possible to prevent abnormal temperature rise of the catalyst and reduce degradation of the catalyst due to aging.
[0062] The average height of the burrs 2A and 3A after shape adjustment (hereinafter also referred to as the average height L of the burrs) is 0.1 μm or more and 30 μm or less, preferably 0.5 μm or more and 20 μm or less. By adjusting the height of the burrs 2A and 3A to 0.1 μm or more and 30 μm or less, the reaction source effect can be exerted.
[0063] When the average height L of the burrs is reduced to less than 0.1 μm, the heat energy accumulated in the burrs 2A, 3A becomes too small to fully exert the reaction source effect. When the average height L of the burrs becomes greater than 30 μm, the tips of the burrs 2A, 3A protruding through the catalyst layer 20 come into contact with the gas to release heat; therefore, the reaction source effect becomes difficult to exert, and the exhaust gas comes into contact with the burrs 2A, 3A to generate turbulence and increase pressure loss. By limiting the average height L of the burrs to 0.5 μm or more and 20 μm or less, the above-mentioned reaction source effect and the like can be more easily obtained.
[0064] Figure 6is a plan view of the catalytic converter 1 when viewed from the axial direction. Referring to this figure, the average height L of the burrs can be found by cutting the converter 1 along a plane including the central axis ("CS" shown by a dotted line) and measuring the height of each burr appearing on this cut surface using image analysis, then summing up these measured values, and further dividing this summed value by the number of measurements. When the measurement is performed, it is expected that the air flow channel (gap) of the honeycomb body 4 is filled with resin. The burr height can be found based on the difference between the foil thickness of the metal foil and the length from one end of the foil thickness direction of the metal foil to the tip of the burr.
[0065] As another measurement method, the burr height of each hole 8 can be obtained by unwinding the honeycomb body 4 and then imaging the metal foil (the base material of the flat foil 2 or the corrugated foil 3) by an image size measuring device equipped with an imaging device (CMOS sensor, etc.) to obtain an image along the circumferential direction of the hole 8. In this case, the average height L of the burr can be obtained by dividing the total value of the measured burr heights by the number of measurements.
[0066] Furthermore, after the honeycomb body 4 is unwound, the burr height of each hole 8 formed in the metal foil (the base material of the flat foil 2 or the corrugated foil 3) can be obtained using a micrometer. The average height L of the burr can be obtained by dividing the total value of the measured burr heights by the number of measurements.
[0067] Will refer to Figure 7 An adjustment method for adjusting the shape of the burrs 2A, 3A will be described. Figure 7 1 is a schematic diagram of the shape adjustment device as viewed from the feeding side of the metal foil. The shape adjustment device 100 includes a driving roller 101, a driven roller 102, a driving motor 103, a transmission mechanism 104, a fixed bracket 105, a hydraulic mechanism 106, and a digital indicator 107. The driving motor 103 is connected to the driving roller 101 via the transmission mechanism 104, and when the driving motor 103 is operated, the driving force of the driving motor 103 is transmitted to the driving roller 101 via the transmission mechanism 104, whereby the driving roller 101 rotates around the rotation axis L1.
[0068] The driven roller 102 is arranged just above the driving roller 101, and is pushed toward the approach side of the driving roller 101 by the hydraulic mechanism 106. Therefore, the driven roller 102 rotates together with the driving roller 101. The metal foil can slide into between the driving roller 101 and the driven roller 102 (i.e., the nip part).
[0069] The nip pressure between the driving roller 101 and the driven roller 102 can be adjusted by a hydraulic mechanism 106. The nip pressure can be measured by an indicator 107. A guide roller not shown is arranged upstream of the driving roller 101 and the driven roller 102. The hydraulic mechanism 106, the gear box 104 of the transmission mechanism, and the drive motor 103 are fixed to a fixed bracket 105.
[0070] In the above configuration, a metal foil having holes with burrs formed by a punching device is prepared, and this foil is fed via a guide roller not shown into the nip portion between the driving roller 101 and the driven roller 102. The driving roller 101 is rotated clockwise when viewed from the driving motor 103 side, the metal foil is pulled into the nip portion between the driving roller 101 and the driven roller 102, and the driving roller 101 (driven roller 102) comes into contact with the burrs of the metal foil.
[0071] When the driving roller 101 and the driven roller 102 are further rotated, the burrs are squeezed and crushed by these rollers to form the narrow portion 50 of the burrs 2A, 3A. It is preferable to obtain the nip line pressure for forming the burrs 2A, 3A in advance as needed by experiments or the like. It is to be noted that the metal foil for the corrugated foil 3 is conveyed to the corrugated foil forming step after the shape is adjusted by the shape adjustment device 100. In the corrugated foil forming step, for example, the corrugated foil 3 can be manufactured by bringing a gear having a shape corresponding to the shape of the corrugated foil into contact with the metal foil to plastically deform this metal foil.
[0072] The shape adjustment method of the burrs 2A and 3A is not limited to the method performed by the shape adjustment device 100; for example, in the stamping step of the metal foil, the shape adjustment can be performed by arranging a baffle to reduce the protrusion of the burrs. In this case, the burrs formed during stamping abut against the baffle and are plastically deformed, so that a shape such as Figure 2 The burrs 2A and 3A are shown.
[0073] The thickness of the catalyst layer 20 can be appropriately set in relation to the average height L of the burrs. That is, as described above, as the amount of the protrusion of the burrs 2A, 3A protruding from the catalyst layer 20 becomes larger, the degradation of the reaction source effect and the generation of turbulence become more significant. Therefore, when the thickness of the catalyst layer 20 is set to be equal to or greater than the average height L of the burrs or when the average height L of the burrs is greater than the catalyst layer 20, it is preferred to limit the difference between the average height L of the burrs and the thickness of the catalyst layer (equivalent to a predetermined amount) to 20 to 10 μm or less.
[0074] Here, when the average pore diameter of the pores 8 is defined as D, the average pore diameter D is 0.2 mm or more and 4.0 mm or less. The pore diameter of each pore 8 is the diameter of the pore. When the average pore diameter D falls below 0.2 mm, the productivity of the catalytic converter 1 may decrease.
[0075] When the average pore diameter D is greater than 4.0 mm, the sum of the edge lengths of the pores 8 (i.e., the total edge length of the pores 8 in the entire honeycomb body 4) becomes smaller, and even by providing burrs, the total length of the burrs is too short to sufficiently improve the emission control performance. It should be noted that if the average pore diameter D falls below 1.1 mm, there is a possibility that the catalyst closes the pores 8 to reduce the emission control performance. Therefore, in the case where the average pore diameter D is less than 1.1 mm, it is desirable to use a catalyst having a low viscosity.
[0076] In the above embodiment, the shape of each hole 8 is illustrated as a circle; however, this may be other shapes. Other shapes may include various shapes such as an ellipse or a rectangle. In any of these shapes, the aperture diameter can be obtained by converting the area into a circle.
[0077] The hole diameter of each hole 8 can be controlled by the punch diameter and the die diameter of the die. The hole diameter of each hole 8 does not have to be the same; however, from the viewpoint of ease of machining, etc., it is preferred to manufacture the holes so that the standard deviation σ is 0.001 mm or more and 0.5 mm or less.
[0078] When the aperture ratio of the hole 8 is defined as R, the aperture ratio R is 5% or more and 70% or less, and preferably 20% or more and 70% or less. Here, the aperture ratio R is a value calculated as a ratio of the sum of the areas of the blackened holes to the total area surrounded by the triangle, as shown in FIG. Figure 8 That is, when a triangle is drawn by connecting the centers of three adjacent holes 8 with a line and the area within the triangle is defined as the total area, and the area of the portion where the triangle overlaps with the hole 8 is defined as the hole area, the ratio of the hole area to the total area is defined as the aperture ratio R.
[0079] When the aperture ratio R decreases to less than 5%, the sum of the edge lengths of the holes 8 becomes too small to sufficiently improve the emission control performance even by providing the burrs. When the aperture ratio R is greater than 70%, the rigidity of the honeycomb body 4 becomes reduced, so that cracking and breaking of the flat foil 2 and the corrugated foil 3 may cause early failure of the catalytic converter 1.
[0080] (Variation Example)
[0081] A modification of the present invention will be described. In catalytic converter 1 of the present modification, burrs 2A, 3A include burrs having no narrow portion.
[0082] In this modification, for the sake of convenience, the burr having a narrow portion (that is, Figure 4 The burr shown in FIG. 1 is referred to as burr V1, and the burr without a narrow portion (that is, Fig. 9 The burr shown in FIG. 1 is called burr V2.
[0083] The present inventors have confirmed that, as the pressure of the roller press increases, the burr V1 relatively decreases and the burr V2 relatively increases.
[0084] Likewise, in the catalytic converter 1 in which the burrs V1 and V2 are mixed, the same effects as those of the first embodiment, such as the reaction source effect, can be obtained by satisfying predetermined numerical conditions.
[0085] Although already described in the first embodiment, the predetermined numerical conditions are described again, and these conditions are 0.2 mm≤D≤4.0 mm, 5%≤R≤70%, 0.1 μm≤L≤30 μm.
[0086] Fig. 9 5 is a photograph of the burr V2. Referring to this figure, the burr V2 is the same as the burr V1 in that the tip end surface extends in a direction orthogonal to the protruding direction of the burr, and is different from the burr V1 in that the burr V2 does not have the narrow portion 50.
[0087] This can be inferred that when the needle-shaped burr is pressed by the shape adjustment device 100 while the hydraulic pressure of the hydraulic mechanism 106 is increased, a narrow portion (such as the narrow portion of the burr V1) is first formed, and when the pressure is further increased, the narrow portion is broken into a step-shaped burr without a narrow portion 50, such as Fig. 9 shown.
[0088] When the burrs V1 and V2 are mixed as in the present embodiment, the burr heights may be obtained without distinguishing these burrs so as to calculate the average height L of the burrs.
[0089] (Second Embodiment)
[0090] Reference Fig.10 A second embodiment of the present invention is described. Fig.10 and Figure 2 , and is a cross-sectional view of a portion of a honeycomb body. Components having common functions with the first embodiment are denoted by the same reference numerals. In the burrs 2A, 3A of the present embodiment, the shape adjustment step is not performed, and the average height L of the burrs 2A is set to 0.1 μm or more and 30 μm or less. Specifically, by increasing the punching speed of the punch, the height of the burrs 2A can be reduced and the average height L of the burrs 2A can be reduced to 0.1 μm or more and 30 μm or less. The punching speed of the punch is preferably 100 mm / sec or more.
[0091] Therefore, the burr 2A of the present embodiment has a general burr shape with a sharp tip (i.e., a needle-like tip), which is different from the burr shape of the first embodiment having a tip surface extending in a direction orthogonal to the protruding direction of the burr. The other configurations are the same as those of the first embodiment; therefore, a detailed description of the other configurations is omitted, but is summarized as follows.
[0092] The thickness and material of the metal foil forming the flat foil 2 and the corrugated foil 3, the catalyst, and the cover 5 are the same as those in the first embodiment. In addition, the second embodiment is similar to the first embodiment in that an oxide coating film containing α-alumina is also formed on the flat foil 2 and the corrugated foil 3 (including burrs).
[0093] The burr average height L of the burrs 2A, 3A is preferably 0.5 μm or more and 20 μm or less, which is the same as the burr average height in the first embodiment. The method of measuring the burr average height L is also the same as in the first embodiment.
[0094] As the amount of the protruding portion of the burrs 2A, 3A protruding from the catalyst layer 20 becomes larger, the degradation of the reaction source effect and the generation of turbulence become more significant. Therefore, when the thickness of the catalyst layer 20 is set to be equal to or greater than the burr average height L, or when the burr average height L is greater than the catalyst layer 20, it is preferred to set the difference between the burr average height L and the thickness of the catalyst layer 20 (equivalent to the predetermined amount) to 10 μm or less.
[0095] The average pore diameter D is 0.2 mm or more and 4.0 mm or less, which is also the same as in the first embodiment. The shape of the hole 8 is not limited to a circle as in the first embodiment. It is preferred that the hole is manufactured so that the standard deviation is σ 0.001 mm or more and 0.5 mm or less, which is the same as in the first embodiment. The aperture ratio R of the hole 8 is 5% or more and 70% or less, preferably 20% or more and 70% or less, which is the same as in the first embodiment.
[0096] As described above, by providing the burrs 2A and 3A of the present embodiment, the same effects as those of the first embodiment can be obtained.
[0097] Example
[0098] (Example 1)
[0099] In the examples of the embodiments of the present invention, the emission control performance, the degradation of the catalyst and the pressure loss performance were evaluated by making various changes to the average burr height L. Table 1 shows the results of the evaluation. The emission control performance was evaluated by T80°C (i.e., T80°C before aging). T80°C is the temperature at which the CO conversion rate (%) reaches 80% based on the CO conversion rate-temperature curve. The simulated gas was heated to 100,000 h. -1 The SV (space velocity) of 10000 ℃ was fed through the catalytic converter, the simulated gas was gradually heated from room temperature using a heater, and the CO conversion rate (%) at each temperature was measured to obtain a CO conversion rate-temperature curve. THC (propylene, C3H6): 550ppm (1650ppmC), NO: 500ppm, CO: 0.5%, O2: 1.5%, H2O: 10%, N2: balance gas was used to simulate diesel exhaust. As T80℃ decreases, the emission control performance of the catalytic converter can be evaluated as higher.
[0100] The degradation of the catalyst was evaluated based on the difference between "T80°C after aging" and "T80°C before aging". "T80°C after aging" was obtained by heating the catalytic converter under heating conditions including heating temperature: 980°C and heating time: 20 hours, cooling the catalytic converter to room temperature, and then measuring T80°C by the method already described. As the difference decreases, the degradation of the catalyst can be evaluated to be lower.
[0101] The pressure loss performance was evaluated by: 3 Dry 25°C N2 gas was applied at a flow rate of / min and the pressure difference before and after the catalytic converter was measured.
[0102] As the metal foil for the corrugated foil and the flat foil, a ferritic stainless steel containing 20 mass % of Cr, 5 mass % of Al and the balance of Fe and inevitable impurities was used. The thickness of the metal foil was 30 μm. Using a punch press, holes were formed in the area of the honeycomb body other than the end (the corresponding range of 5 mm from the exhaust inlet side and from the exhaust outlet side). The average burr height L was controlled by adjusting the punching speed of the punch press without performing height adjustment by the shape adjustment device. The average burr height L was controlled by adjusting the punching speed of the punch press as described in reference to FIG. Figure 6 The method described in the embodiment is measured (this also applies to other embodiment examples described later).
[0103] The area of the metal foil where the holes are formed is imaged from the foil thickness direction of the metal foil, and the outline of the holes is converted into data; and thereafter, the hole diameter is converted into a circle diameter by computer processing to obtain the hole diameter. The aperture ratio R is obtained by the method in the above embodiment.
[0104] After corrugating the metal foil obtained by the above treatment into a corrugated foil, the corrugated foil having a brazing material in an appropriate position is overlapped on the coated flat foil, and the foils are wound together and heat-treated (brazed) to thereby produce a honeycomb body. The diameter of the honeycomb body is 35 mm, and the axial length is 80 mm. The cell density is 400 cpsi. The honeycomb body thus produced is inserted into an outer cover and fixed to the outer cover by brazing to provide a catalytic converter. The diameter of the catalytic converter is 38 mm, and the axial length is 80 mm.
[0105] A washing liquid containing ceria-zirconia-lanthanum oxide-aluminum oxide as main components and 1.25 g of palladium per 100 g was passed through the honeycomb, and excess washing liquid was removed; and thereafter, the honeycomb was dried at 180°C for 1 hour and then baked at 500°C for 2 hours to form a catalyst layer with a thickness of 20 μm on the honeycomb.
[0106] It should be noted that, if necessary, the viscosity of the wash solution is adjusted when used so that no pores are closed by the catalyst.
[0107] For No. 3 to No. 10, the oxide coating film was formed by applying heat treatment to the honeycomb body before forming the catalyst layer. The conditions for the heat treatment were heating temperature: 900° C. and heating time: two hours.
[0108] [Table 1]
[0109]
[0110] The emission control performance (T80°C) of No. 1 and No. 3 without burrs is low. No. 2 has higher emission control performance (T80°C) due to burrs, but experiences significantly increased catalyst degradation due to the lack of oxide coating. No. 4 to No. 9 have higher emission control performance (T80°C) due to burrs, and the degradation of the catalyst can also be kept low. In addition, the pressure loss can also be maintained at a low value. No. 10 has burrs that protrude significantly from the catalyst layer (20μm protruding from the catalyst layer), so that the pressure loss increases due to the generation of turbulence, and the emission control performance (T80°C) deteriorates due to the reduction of the reaction source effect.
[0111] (Example 2)
[0112] The thickness of the oxide coating and the content of α-alumina were variously changed, and the emission control performance (T80°C), the degradation of the catalyst and the pressure loss performance were evaluated. The thickness of the oxide coating and the content of α-alumina were adjusted by adjusting the heat treatment conditions for forming the oxide coating within the following ranges: heating temperature: 1000°C to 1100°C and heating time: 5 minutes to 20 hours. As in Example 1, the average height L of the burr was standardized to 5 μm by adjusting the punching speed of the punch press without performing height adjustment by the shape adjustment device. The foil thickness of the metal foil is 40 μm. The diameter of the honeycomb is 40 mm and the axial length is 60 mm. The cell density is 400 cpsi. The resulting honeycomb is loaded into the outer cover and fixed by brazing to provide a catalytic converter. The diameter of the catalytic converter is 43 mm and the axial length is 60 mm. The pore size and pore size ratio are unified to 2 mm and 50%, respectively. Other conditions are similar to those of Example 1.
[0113] [Table 2]
[0114]
[0115] With respect to No. 12, the thickness of the oxide coating film reached only 0.03 μm, so that the degradation of the catalyst increased. With respect to No. 18, the thickness of the oxide coating film exceeded 2.0 μm, so that the evaluation of T80°C after aging could not be performed due to the occurrence of foil cracking. With respect to No. 19, the α-alumina contained in the oxide coating film was as little as 5% by mass, so that the degradation of the catalyst increased. It has been found from this example that the formation of an oxide coating film containing at least 10% by mass of α-alumina of 0.05 μm to 2 μm makes it possible to effectively reduce the degradation of the catalyst.
[0116] (Example 3)
[0117] In this embodiment, various changes were made to the average pore size D and the pore size ratio R, and the resulting emission control performance (T80°C), pressure loss performance, and degradation of the catalyst were evaluated. As in Example 1, the average burr height L was unified to 8 μm by adjusting the punching speed of the punch press without performing height adjustment by the shape adjustment device. The foil thickness of the metal foil is 50 μm. The diameter of the honeycomb body is 51 mm and the axial length is 120 mm. The cell density is 300 cpsi. The resulting honeycomb body is loaded into an outer cover and fixed by a brazing process to provide a catalytic converter. The diameter of the catalytic converter is 54 mm and the axial length is 120 mm.
[0118] [Table 3]
[0119]
[0120] Referring to No. 24 to No. 30, it has been found that providing burrs makes it possible to ensure the desired emission control performance (T80°C) even if the average pore diameter D is small. With respect to No. 31, since the average pore diameter D is too large and the total length of the burrs is short, it is not possible to improve the emission control performance (T80°C). With respect to No. 32, since the aperture ratio is too small and the total length of the burrs is short, it is not possible to improve the emission control performance. With respect to No. 41, the aperture ratio exceeds 70%, and foil cracking of the metal foil is seen after aging, so the degradation of the catalyst is not evaluated.
[0121] (Example 4)
[0122] In this embodiment, the test was performed under similar conditions to those of Embodiment 1, except that the shape adjustment device was used to adjust the burr average height L. It should be noted that, for No. 45 to No. 46, about 30% were observed to be burrs V2 and the rest were burrs V1 having a narrow portion. For No. 46 to No. 51, the burrs V1 having a narrow portion were dominant.
[0123] [Table 4]
[0124]
[0125] No. 42 and No. 44, which have no burrs, have lower emission control performance (T80°C). No. 43 has higher emission control performance (T80°C) due to the burrs, but experiences significantly increased catalyst degradation due to the lack of an oxide coating. Nos. 45 to 50 have higher emission control performance (T80°C) due to the burrs, and the degradation of the catalyst can also be kept low. In addition, the pressure loss can also be maintained at a low value. No. 51 has burrs that protrude significantly from the catalyst layer (20 μm protruding from the catalyst layer), so that the pressure loss increases due to the generation of turbulence, and the emission control performance (T80°C) deteriorates due to the reduction of the reaction source effect.
[0126] (Example 5)
[0127] In this embodiment, the test was performed under similar conditions to those of Embodiment 2, except that a shape adjustment device was used to adjust the average height L of the burrs.
[0128] [Table 5]
[0129]
[0130] With respect to No. 53, the thickness of the oxide coating film reached only 0.03 μm, causing increased degradation of the catalyst. With respect to No. 59, the thickness of the oxide coating film exceeded 2.0 μm, making it impossible to conduct the evaluation of T80°C after aging due to the occurrence of foil cracking. It has been found that forming an oxide coating film of 0.05 μm to 2 μm containing at least 10% by mass of α-alumina enhances emission control performance and makes it possible to reduce pressure loss and reduce degradation of the catalyst.
[0131] (Example 6)
[0132] In this embodiment, the test was performed under similar conditions to those of Embodiment 3, except that a shape adjustment device was used to adjust the average height L of the burrs.
[0133] [Table 6]
[0134]
[0135] Referring to No. 65 to No. 71, it has been found that providing burrs makes it possible to ensure the desired emission control performance (T80°C) even if the average pore diameter D is small. With respect to No. 72, since the average pore diameter D is too large and the total length of the burrs is short, it is not possible to improve the emission control performance (T80°C). With respect to No. 73, since the aperture ratio is too small and the total length of the burrs is short, it is not possible to improve the emission control performance (T80°C). With respect to No. 82, the aperture ratio exceeds 70%, and foil cracking of the metal foil is seen after aging, so the deterioration of the catalyst is not evaluated.
[0136] Reference numerals list
[0137] 1 Catalytic converter
[0138] 2 Flat foil
[0139] 3 Corrugated foil
[0140] 4 Honeycomb body.
Claims
1. A honeycomb type metal substrate formed by alternately laminating metal flat foils and metal corrugated foils, The metal flat foil and the metal corrugated foil each include a plurality of holes penetrating the foil in a thickness direction, A burr with a small height is formed on the edge of each hole, In the metal flat foil and the metal corrugated foil, at least the surface of the burrs is covered with an oxide coating film containing α-aluminum oxide, The burr formed on the metal flat foil is formed only on one side of the metal flat foil, rather than on both sides of the metal flat foil. The burrs formed on the metal corrugated foil are formed only on one side of the metal corrugated foil, rather than on both sides of the metal corrugated foil. When a triangle is drawn by connecting the centers of three adjacent holes with a line and the area within the triangle is defined as the total area, and the area of the portion where the triangle overlaps with the hole is defined as the hole area, the ratio of the hole area to the total area is defined as the aperture ratio R, when the average aperture of the plurality of holes is defined as D, and the average height of the burr is defined as L, the following equations (1) to (3) are satisfied, 0.2 mm ≤ D ≤ 4.0 mm (1) 5%≤R≤70%(2) 0.1μm≤L≤30μm(3) 2. The honeycomb metal substrate according to claim 1, wherein The tip end surface of each burr is formed into a shape extending in a direction orthogonal to the protruding direction of the burr.
3. The honeycomb metal substrate according to claim 2, wherein The burrs have narrow portions each having a smaller width than the tip end surface.
4. The honeycomb metal substrate according to any one of claims 1 to 3, wherein The average height L of the burr satisfies the following equation (4): 0.5 μm≤L≤20μm(4) 5. The honeycomb metal substrate according to any one of claims 1 to 3, wherein The oxide coating film has a thickness in the range of 0.05 μm to 2 μm, and contains at least 10% by mass or more of α-alumina.
6. A catalytic converter comprising: The honeycomb metal substrate according to any one of claims 1 to 3; as well as a catalyst layer supported on the metal flat foil and the metal corrugated foil, The average height L of the burrs is less than the thickness of the catalyst layer or is greater than the thickness of the catalyst layer by a predetermined amount, and The predetermined amount is 10 μm or less.
7. A catalytic converter comprising: The honeycomb metal substrate according to claim 4; as well as a catalyst layer supported on the metal flat foil and the metal corrugated foil, and An average height L of the burrs is smaller than a thickness of the catalyst layer.
8. The catalytic converter according to claim 6 or 7, wherein: The oxide coating film has a thickness in the range of 0.05 μm to 2 μm, and contains at least 10% by mass or more of α-alumina.
Citation Information
Patent Citations
Catalyst carrier made of metal
JP2005313083A
Catalytic converter for cleaning exhaust gas
JP2007203256A
Honeycomb substrate for catalyst support, and catalytic converter for exhaust gas purification
CN110337329A
Exhaust gas purging device using metallic base material and method for manufacturing exhaust gas purging device
CN111263661A
Rare-earth catalyzer using alloy cellular carrier and its preparation
CN86105768A